Percepções de um grupo de professores que ensinam matemática sobre o pacto nacional pela alfabetização na idade certa (pnaic) - Simão, Lúcia Eneida de Sousa Alves (2019)
This qualitative research was carried out with the participation of a group formed by five teachers who teach at a municipal public school in the city of Uberlândia, Minas Gerais, Brazil. The focus of interest in this study is Mathematical Literacy and the course offered by the Program National Pact for the Right Age (Pacto Nacional pela Idade Certa-PNAIC), in 2014. The survey was guided by the following question: How do a group of teachers in a public school in Uberlândia, Minas Gerais perceive the didactical and pedagogical guidelines of PNAIC in Mathematical literacy in their practices? The study aimed to investigate, to analyze and to understand how the teachers, subjects of this survey, receive the PNAIC’s guidelines in Mathematical Literacy in their teaching practice. The analysis material consisted of a Questionnaire, Written Records, a Notepad, Reflective Sessions and the Field Notes of the researcher. The Written Records on pedagogical practice contributed significantly to the teachers’ understanding of the complexity of teaching practice and the processes that involve it. We considered as very important the writing and voice of each participating teacher as well their sharing of experiences and the space for reflection. Along the study we noted that the participation of the teachers in PNAIC has contributed for the expansion and the improvement of their professional knowledges as well it provided an approximation with their peers, strengthening team spirit. Based on the research’s goal and problem, it was elucidated that the teachers' perceptions about the PNAIC were significant for personal and professional growth, providing changes and permanence in their pedagogical practices We verified the importance of a continuous training work that appreciates the collaboration and the involvement of the professionals in search of new perceptions, as well as the necessity of the continuity of the offer of courses and studies for the teachers. The present work intends to bring contributions regarding the formation of teachers who teach Mathematics in the first years of Elementary School, so that the knowledge related to teaching and learning contemplate, in an articulated and cohesive way, theory and practice.